De novo deletion of TBL1XR1 in a child with non‐specific developmental delay supports its implication in intellectual disability. Issue 9 (28th May 2014) - Tabet, Anne‐Claude; Leroy, Camille; Dupont, Céline; Serrano, Emilie; Hernandez, Karen; Gallard, Jennifer; Pouvreau, Nathalie; Gadisseux, Jean‐François; Benzacken, Brigitte; Verloes, Alain
<x xml:space="preserve">Abstract</x> We report on a 6‐year‐old child with a de novo 1.6 Mb deletion in the 3q26.31q26.32 region identified by SNP array, involving only one relevant gene: TBL1XR1. The girl shows non‐specific, mild to moderate intellectual deficiency but no autistic behavior. Point mutations in TBL1XR1 have recently been implicated in three patients with intellectual disability (ID) and autistic features. Our report supports that haploinsufficiency for TBL1XR1 could be implicated in non‐ASD autosomal dominant ID. © 2014 Wiley Periodicals, Inc.